Strategi Pengelolaan Sumber Daya Alam Berbasis Pembangunan Berkelanjutan: Penelitian - Nababan, Alexa Angelica; Hutabarat, William Barker; Simanjuntak, Rouli Pranatalia; Fajri, M Yudi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This article discusses the role of natural resources (NR) in driving Indonesia's national economy. Natural resources (NR) are one of the main pillars of a country's economy. Sustainable development offers an integrative approach that emphasizes the importance of balancing current needs with the continuity of future generations. In this context, natural resource management strategies must include conservation-based planning, the use of environmentally friendly technologies, empowerment of local communities, and synergy among stakeholders. This study aims to examine various natural resource management strategies that align with sustainable development principles and provide policy recommendations that can be implemented at local and national levels. The results of the study are expected to contribute to formulating more just, efficient, and sustainable natural resource management policies